IDENTIFIKASI FLORA YANG BERPOTENSI SEBAGAI TANAMAN OBAT DI KAWASAN HUTAN CAGAR ALAM NAPABALANO KABUPATEN MUNA - Alamsyah Flamin; Sahindomi Bana; Djiondan Taruna (Jurnal Ecogreen, 2015)
This research is aim to know the kinds of medical plants, and usage in the Forest Preserve Napabalano Muna. The research was conducted at the Forest Preserve Napabalano in Napabalano , District Napabalano , Muna District , Southeast Sulawesi.  There are 11 of medical plants at Napabalano Forest Nature Reserve that used by people at the surounding of the forest.   And the part of the trees that used by the people are stem, root, flower, bark, resin, and leaf sap of the trees. This part has been known from generation to generation. The  Knowledge of the people about the way of using depend on the kind of the trees, how to use herbs that are crushed, squeezed, drunk directly, soaked in the boiled water and  boiled alone or in a mixture. Keywords : Napabalano Forest Preserve, Medical Plants